DOI: 10.4995/thesis/10251/86185
|View full text |Cite
|
Sign up to set email alerts
|

ESTUDIO PARA LA MEJORA DE LAS TÉCNICAS DE PROPAGACIÓN DE LA ALCAPARRA (Capparis spinosa L.).

Abstract: Caper (Capparis spinosa L.) is a plant cultivated especially for its flower buds (capers), which are included in the Mediterranean diet. The main producing areas are in the more arid environments of Morocco, Iberia, Turkey and the Italian islands of Pantelleria and Salina.xvii

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 76 publications
3
17
0
Order By: Relevance
“…The trials were judged as satisfactory when the difference between the maximum and minimum germination percentages of the four replications did not exceed the tolerance established by [27]. For the analysis of the germination curves of each repetition, according to studies carried out previously by [14,30], the model that best fits is that of the logistic function proposed by [31] and has the following expression:…”
Section: Germinationmentioning
confidence: 99%
See 4 more Smart Citations
“…The trials were judged as satisfactory when the difference between the maximum and minimum germination percentages of the four replications did not exceed the tolerance established by [27]. For the analysis of the germination curves of each repetition, according to studies carried out previously by [14,30], the model that best fits is that of the logistic function proposed by [31] and has the following expression:…”
Section: Germinationmentioning
confidence: 99%
“…Although the fruits contain many seeds, they have a very low germination percentage. Several authors have reported various studies to improve its germination and try to break the possible physical dormancy with different types of scarification, whether mechanical, chemical, thermal, or biological, [12][13][14][15], as well as being able to break the physiological dormancy with the use of gibberellic acid (GA 3 ) and potassium nitrate, as reported by [16][17][18][19]. It has been proven that scarification with sulfuric acid and the addition of GA 3 have improved the germination percentage [12,20], which Plants 2022, 11, 202 2 of 10 has led to the hypothesis that caper seeds can present physical dormancy (due to the impermeability of their cover) and physiological dormancy imposed by the embryo.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations